Energy consumption, capital investment and environmental degradation: The African experience - Ekundayo P. Mesagan; Chidi N. Olunkwa (African Governance and Development Institute (AGDI), 2020)
This study investigates the effects of energy consumption and capital investment on environmental degradation in selected African countries between 1981 and 2017 using panel cointegration approaches. The Fully Modified and the Dynamic Ordinary Least Squares results affirm that energy consumption positively affects carbon emissions in Algeria, Nigeria, Morocco, and in the panel. At the same time, both also confirm that capital investment positively and significantly impacts carbon emissions in the region. Again, results show that capital investment augments energy use to reduce carbon emissions in Africa significantly. This implies that capital investment can provide needed impetus to reduce environmental degradation in the continent. The study, therefore, recommends that African countries should focus on energy conservation policies to reduce the adverse effect of energy use on carbon emissions.
Keywords: Q40; Q42; Q43; Q54; Q57; 330; Electricity Consumption; Capital investment; Environmental Degradation; Africa